KrishiGrow: An Expert System Based Macro and Micronutrient Visualization System for Smart Crop Management - Mondal, Sayanton; Roy, Debarshi; Ganguly, Sreetam; Bhowmick, Rubi; Sethi, Rithwick; Banerjee, Santanu; Sutar, Debamita (Journal of Agricultural Extension Management, 2021)
Macro and micronutrient management of agricultural land is a problem that requires constant monitoring and planning, which is absent in the current Indian agricultural landscape. Farmers often balance the risk of biomagnification and nutrient depletion with maximizing profits, which is not done correctly in most cases. Continuous depletion of macro and micronutrients from the farming land would lead to poor soil fertility, reduced crop production, and negatively impact human and animal health. In this article, we propose KrishiGrow, an expert monitored smart system that utilizes open-source data from agricultural extension information outlets and geological surveys across India and presents the farmer with the most accurate and up-to-date advice on the strain and type of crop that should be planted for a particular plot of land. Our solution would also enable the farmers with the most updated data on soil quality and fertility across India. We believe that KrishiGrow and its implementation will aid small and mid-level farmers to obtain the highest possible productivity for their land.